Influence of dutasteride treatment on serum hormone levels and aging male symptoms in patients with benign prostatic enlargement. (3rd October 2017) - Maeda, Takahiro; Kikuchi, Eiji; Hasegawa, Masanori; Homma, Keiko; Ando, Toshiyuki; Suzuki, Kenjiro; Kaneko, Gou; Mizuno, Ryuichi; Miyajima, Akira; Oya, Mototsugu
Abstract : Objectives: To clarify the effects of dutasteride on serum hormone levels and aging male symptoms in patients with benign prostatic enlargement. Methods: The present prospective study was carried out in 110 symptomatic benign prostatic enlargement patients treated with daily administration of 0.5 mg dutasteride. We analyzed serum hormonal levels and aging related symptoms using a validated Aging Male Symptom questionnaire at baseline and after 3 months of dutasteride treatment. Results: The mean total testosterone, free testosterone and luteinizing hormone levels after dutasteride treatment were approximately 20% higher than those at baseline. The percentage increases in total and free testosterone levels were negatively correlated with these baseline levels. Baseline age, levels of total testosterone and free testosterone, and the changes in the rate of luteinizing hormone after dutasteride treatment tended to be correlated with an increase in the rate of total testosterone and free testosterone after dutasteride treatment. In a subgroup of 26 patients with moderate‐to‐severe aging male symptoms, poor morning erection and free testosterone levels <8.5 pg/mL, total aging male symptoms, and somatic symptoms scores significantly decreased after dutasteride treatment with an increase of total and free testosterone. Conclusions: The increase of endogenous free testosterone and total testosterone by dutasteride might bring additional benefits of improvement of aging male‐related symptoms, especially in patients with lower free testosterone baseline levels and moderate‐to‐poor aging‐related symptoms.